COVID-19 Prevention: Healthy and Clean-Living Behavior Program on Toilet Access in Tiban New Village, Batam City, Indonesia - Hengky Oktarizal; Yuanita Windusari; Irfannuddin Irfannuddin; R. Kintoko Rochadi; Ahmadi Ahmadi; Roni Saputra; Mega Gemala (Universitas Airlangga, 2022)
Background: The current low level of prevention of COVID-19 is one of the severe problems in Indonesia. Healthy and Clean-Living Behavior or PHBS (Perilaku Hidup Bersih dan Sehat) program and sanitation access are some things that can be done in terms of prevention during a pandemic. New Tiban Village ranks 3rd with the highest number of COVID-19 cases in Batam City. Objective: This study aims to determine whether there was a relationship between implementing the Healthy and Clean-Living Behavior program and toilet access on the incidence of COVID-19 in New Tiban Village, Batam City, Indonesia. Methods: A quantitative analytic observational study with a total sample of 115 families. The instrument used in this study was a questionnaire. The acquired data were analyzed with chi-square analysis using SPSS as the tool. Results: The results showed a significant relationship between the application of the Healthy and Clean-Living Behavior program towards COVID-19 cases p = 0.006. There was an effective relationship between toilet access towards COVID-19 cases p = 0.000. Conclusion: In this study, there was a significant relationship between applying the Healthy and Clean-Living Behavior program and toilet access toward COVID-19 with a value of α < 0.05. Recommendations for the community include always carrying out health protocols by maintaining distances and always washing hands using running water and soap after activities outside the home.